(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Starting from the dialogue between dance pieces and literature works in which there is an intimate relationship between art and life, this essay analyzes some creations that propose an invitation, both to the performer/writer and to the spectator/reader, to the perception of oneself in drift. In his lecture “Poetry and abstract thought”, Paul Valéry suggested the separation between prose and poetry; although, in contemporary, poets and choreographers break this separation by mixing movement and language experiences from both the fields of ordinary life and art. Based on the interest of choreographers in walking as a fundamental experience for dance, we reflect on the presence of prose (and prosaism) in contemporary poetry production.